2002
DOI: 10.1046/j.1462-2920.2002.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and comparative analysis of the metabolically versatile Pseudomonas putida KT2440

Abstract: Pseudomonas putida is a metabolically versatile saprophytic soil bacterium that has been certified as a biosafety host for the cloning of foreign genes. The bacterium also has considerable potential for biotechnological applications. Sequence analysis of the 6.18 Mb genome of strain KT2440 reveals diverse transport and metabolic systems. Although there is a high level of genome conservation with the pathogenic Pseudomonad Pseudomonas aeruginosa (85% of the predicted coding regions are shared), key virulence fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
733
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,220 publications
(740 citation statements)
references
References 56 publications
5
733
2
Order By: Relevance
“…Cell-cell communication has been recently shown to take place during bacterial colonization of the tomato rhizosphere, and the production of AHLs in rhizosphere populations has been reported (43). In the soil and rhizospherecolonizing bacterium P. putida KT2440, no production of AHLs has been detected to date, and there was no genetic evidence that this microorganism possesses a quorum-sensing system (32). The results presented here indicate that KT2440 does respond to population density via a still-unidentified signaling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cell communication has been recently shown to take place during bacterial colonization of the tomato rhizosphere, and the production of AHLs in rhizosphere populations has been reported (43). In the soil and rhizospherecolonizing bacterium P. putida KT2440, no production of AHLs has been detected to date, and there was no genetic evidence that this microorganism possesses a quorum-sensing system (32). The results presented here indicate that KT2440 does respond to population density via a still-unidentified signaling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting strain, EU9, did show increased attachment, but only at early time points; further biofilm development and detachment kinetics were similar to those of the wild-type strain (Fig. 3), indicating that the hyperadherent character of ibi-626 is not solely due to the disruption of olpA, and that an additional mutation might be present.Complete sequencing of ibi-626 reveals a point mutation that affects lapGThe genome of mutant ibi-626 was fully sequenced and compared with the reference genome of KT2440 (Nelson et al, 2002) to define potential mutations that could contribute to the phenotype of this strain. Several apparent discrepancies with respect to the reference sequence were checked by PCR amplification and sequencing of the corresponding region in ibi-626 and our laboratory KT2440 strain.…”
mentioning
confidence: 99%
“…A homology search revealed that orf3 is highly homologous to the putative 3-oxoacyl-(acyl carrier protein [ACP]) synthase III (␤-ketoacyl-ACP synthase III) genes of Escherichia coli, Salmonella enterica serovar Typhimurium, and Pseudomonas putida strain KT2440 (24,36). It has been reported that a 3-oxoacyl-ACP synthase III called FabH is one of the enzymes in the type II fatty acid synthesis system (20).…”
mentioning
confidence: 99%